Learning through mess: Sensemaking visual communication practices in a UK multidisciplinary applied health study. (August 2022) - Robson, Ian
This article addresses the challenges and opportunities associated with the development of new visual communication practices and outputs, using an example of such work conducted in a UK interdisciplinary applied health project. Reflecting on his role as co-researcher and practice as a visual ethnographer in the study, the author argues that new visual communication practices may emerge from 'mess' and even ugliness. In the case discussed, the author comes to terms with mess and elements of failure as potential phenomena of learning through a process of Sensemaking (see Weick's Sensemaking in Organizations, 1995), by applying innovative visual methods to the approach. Through his version of visual Sensemaking, the author identifies a set of principles to inform innovation in collaborative, interdisciplinary visual communication.